COVID-19 and the Rationale for Primary Selective Laser Trabeculoplasty and Diode Laser Transscleral Cyclophotocoagulation in Africa. Issue 4 (8th April 2022) - Milad, Daniel; Mikhail, David; Lenzhofer, Markus; Agré, Jérémie; Toren, Andrew
Abstract : The recent COVID-19 pandemic has affected ophthalmologists' practices worldwide. Consequent global drug shortages and the limitations of medical glaucoma treatments in sub-Saharan Africa have highlighted the need for innovation in global ophthalmology to provide accessible, affordable, and effective glaucoma care. The role of lasers rather than medications for glaucoma patients in developing nations is emerging. Since lasers are easier to master than glaucoma surgery, it is pertinent to discuss the primary use of lasers in treating glaucoma in such nations. In particular, selective laser trabeculoplasty and diode laser transscleral cyclophotocoagulation seem to present a promising future for the treatment of glaucoma in Africa. In this report, we provide an evidence-based discussion exploring the emerging role of lasers in Africa.